Upaya Meningkatkan Kualitas Membaca Al-Qur’an Siswa Kelas Tiga SD Negeri Sitirejo dengan Metode Pembiasaan - Siti Mutoharoh; Siti Fatimah; Faisal Faisal (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
This study aims to determine the efforts to improve the quality of students' reading the Qur'an. The method used is Classroom Action Research by going through the stages of planning, implementing, observing and reflecting. The data is taken based on the results of interviews, observations, and tests. The subjects were 16 grade 3 students of SD Negeri Sitirejo. The results of the study can be concluded that the use of the habituation method of reading the Qur'an and discussion of tajwid can improve the quality of students' reading of the Qur'an, because in each cycle of meetings there is an increase in the percentage of results.